TERATOGENIC EFFECTS OF DRUGS ON THE ORGANISM OF A FUTURE CHILD DURING FETAL STAGE OF DEVELOPMENT - S.A. Sher (Педиатрическая фармакология, 2011)
Article assesses the impact of adverse factors on intrauterine development of the child, first of all, drugs. The author stresses that the importance of drug safety (D) is due to the large number of unintended pregnancies worldwide. A list of the D, providing proven teratogenic effects on a child organism is presenting. It is shown that the D teratogenic effect in humans can not be assessed on the basis of experimental data obtained in animals due to the difference between metabolic and detoxification processes in a different mammals and individuals. Key words: drugs, safety, teratogenic effects, fetal development, the unborn child. (Pediatric pharmacology. — 2011; 8 (6): 57–60).